Load-Carriage Conditioning Elicits Task-Specific Physical and Psychophysical Improvements in Males. Issue 9 (September 2019) - Wills, Jodie A.; Saxby, David J.; Glassbrook, Daniel J.; Doyle, Tim L.A.
Abstract : Abstract: Wills, JA, Saxby, DJ, Glassbrook, DJ, and Doyle, TLA. Load-carriage conditioning elicits task-specific physical and psychophysical improvements in males. J Strength Cond Res 33(9): 2338–2343, 2019—Load carriage is a requirement of many military roles and is commonly used as an assessment of soldier physical readiness. Loaded, compared with unloaded, walking tasks elicit increased physical demands, particularly around the hip joint, which can exceed the initial capacity of military personnel. This study aimed to identify and characterize physical performance responses to a lower-limb focused physical training program targeted toward load-carriage task demands. Fifteen healthy male civilians (22.6 ± 1.5 years, 1.82 ± 0.06 m, and 84.1 ± 6.9 kg) completed a 10-week physical training program consisting of resistance training and weighted walking. A load-carriage task representing the Australian Army All Corps minimum standard (5 km at 5.5 km·h −1, wearing a 23-kg torso-borne vest) was completed before and on completion of the 10-week training program. Heart rate and rating of perceived exertion measures were collected throughout the load-carriage task. The performance measures of countermovement and squat jumps, push-ups, sit-ups, and beep test were performed before, mid-way, and on completion (weeks 0, 6, and 11) of the 10-week training program. Psychophysical performance, as measured by rating of perceived exertion, significantly decreased ( p < 0.05) during the load-carriage task after training, demonstrating improvements in psychophysical responses. The training program resulted in significant increases in squat jump maximal force, push-ups, sit-ups ( p < 0.05), and estimated maximal oxygen uptake ( p < 0.05). Physical performance improvements and positive physiological adaptations to a load-carriage task were elicited in males after completing a 10-week training program. Military organizations could use this evidence-based training program to efficiently train soldiers to improve their load-carriage capacity. Abstract : Supplemental Digital Content is Available in the Text.